A Development of Digital Learning Platform for Malacca High School - Abu Samah, Muhammad Farid; Samsudin, Noor Azah (Applied Information Technology And Computer Science, 2021)
Teaching and learning (T&L) activity is a main thing in the education institution. In Malaysia, this activity fully carried out in physical mode which student have to come to the school for the t&l session. However, Pandemic COVID-19 which contagious make the movement control order (MCO) only the alternative to be taken to prevent this virus from spread in a large scale. Initiative of digital learning platform is therefore created to overcome the obstacles that exist to continue the learning process. Objective toward this development is proposed to develop digital learning platform for Malacca High School (MHS) Community. Student, teacher and school administrator will fully utilize this system for teaching and learning purposes. The platform builds by using prototyping-based methodology will digitalize part of the academic working process of teacher, administrator, and students at school. Digital learning platform is an integrated system in web-based form. All development process take part in this project will use hardware and software tools to ensure the end product match with the estimation project end product and tally with the objective for the project. Software use in this system is Operating System Microsoft Windows 10, atom software as compiler, XAMPP as server that connect source code, MySQL for the database system. Development of this system also make students are able to carry out their responsibilities well as a student and the distribution of work carried out by lecturers indirectly becomes systematic and acceptable to most students. This platform will be pioneer in digitalization in education system in Malaysia. Student will be exposed toward the technology development and experienced while using it. In a nutshell, with the presence of idea and system development from this project, it could help some extent contribute to technology-based development implemented in the national education system.